Ultrasonography of the Fasciae and Common Pathologies: The Game Changer - Carmelo Pirri; Nina Pirri; Veronica Macchi; Andrea Porzionato; Raffaele De Caro; Levent Özçakar; Carla Stecco (Diagnostics)
Ultrasound (US) is rapidly gaining attraction among physicians for the evaluation of fasciae. Unlike traditional imaging, which often lacks specificity of pain localization, US examination stands out as a versatile tool, capable of detecting both structural and functional information. This unique capability allows for a comprehensive assessment of fasciae—the intricate connective tissue essential for human biomechanics. US examination offers a multiparametric approach for the assessment of thickness, echogenicity, stiffness, deformation and shear strain. This comprehensive examination is invaluable for identifying fascial pathologies that may not be detected during physical examination. In this study, we render and discuss common/elementary lesions of the fascia.